Solving Higher Order Ordinary Differential Equation (ODE) by using Differential Transformation Method (DTM) - WAN AZIZ, WAN NUR ATHIRA NASRINA; Abd Latif, Noor Azliza (Enhanced Knowledge in Sciences and Technology, 2022)
The ordinary differential equation (ODE) has been important in the mathematical study. Commonly, higher-order ODEs will be used to form the formulation of a real-world problem. But the higher-order ODEs are complex to solve. Therefore, the differential transformation method (DTM) has been introduced. The DTM is semi numerical method that resolves the equation in the form of a polynomial. This method are proved to reduce the computational work. In this study, two different order of ODEs has been solved by using Maple software. The numerical solution derived by DTM has been compared with the numerical solution from the Adomian decomposition method (ADM) to see the accuracy of the method to the exact value. By the end of the research, the effectiveness of the DTM is proven to solve the higher-order ODEs with the minimum absolute error compared to the other method.